Effect of Magnetic Treatment on Seawater Determined by Quartz Crystal Microbalance: Mechanisms of Crystal Deposition - Alimi, Fathi (Engineering, Technology & Applied Science Research, 2024)
This study investigated the effect of a magnetic field on the crystal deposition of treated seawater to determine the mechanism of calcium carbonate deposition on the quartz surface. Several samples of standard seawater (43 g/L) were circulated through a permanent magnetic field of 0.16 T at a fixed temperature, pH, and flow rate. Scaling experiments showed that magnetic treatment of seawater enhanced the precipitation of calcium carbonate and that two superposed phases were deposited. A first layer formed with crystals of aragonite covering the whole surface of the quartz, and then a second phase of calcite was deposited. In the untreated solutions, only homogeneous agglomerates of aragonite were deposited.